Upregulated solute carrier family 37 member 1 in colorectal cancer is associated with poor patient outcome and metastasis - Kikuchi, Daiki (Oncol Lett, 2018)
Solute carrier (SLC) drug transporters exchange various molecules without energy from adenosine triphosphate hydrolysis, indicating an association with anticancer drug resistance. However, the expression and role of SLC transporters in malignant tumors has not yet been fully elucidated. Therefore, in the current study, the expression of SLC37A family genes was evaluated in patients with colorectal cancer (CRC), and it was revealed that SLC family 37 member 1 (SLC37A1) expression was significantly increased in tumorous tissues compared with that in non-tumorous tissues. The cases with upregulated expression of SLC37A1 by immunohistochemical staining were significantly associated with positive venous invasion and liver metastasis. Furthermore, upregulated SLC37A1 expression was associated with poor overall survival time in the present cohort. These results indicated that SLC37A1 is involved in the hematogenous metastasis of CRC. To investigate whether SLC37A1 is associated with hematogenous metastasis and glycolipid metabolism, SLC37A1 was knocked down in colon cancer cells, and the expression of sialyl Lewis A and sialyl Lewis X was observed to be decreased. In summary, upregulation of SLC37A1 was observed in patients with CRC, and was associated with poor patient outcomes and survival. To the best of our knowledge, the present study is the first to propose a key role of SLC37A1 in CRC, and additional studies are warranted to reveal the functional role of SLC37A1 in CRC development.